A Case of Schizophrenia in a Young Male Adult with no History of Substance Abuse: Impact of Clinical Pharmacists' Interventions on Patient Outcome. (15th February 2020) - Opare-Addo, Mercy N. A.; Mensah, Josephine; Aboagye, Grace Owusu
Abstract : Schizophrenia is a chronic and severe mental disorder characterized by distortions in thinking, perception, emotions, language, sense of self, and behaviour. This report presents the role of clinical pharmacists in the management of a patient diagnosed with schizophrenia with symptoms of paranoia. A gainfully employed young African male adult reported to be roaming around town moving from one bank to another was arrested. The patient was referred to the psychiatric unit of a hospital and diagnosed with schizophrenia. Key interventions offered included rapid tranquilization, electroconvulsive therapy, and psychotherapy. Medications administered to the patient while on admission included IV diazepam, IM haloperidol, IV Ketamine, IM flupentixol, olanzapine tablets, and trihexyphenidyl tablets. Issues raised by clinical pharmacists during the patient's admission included need for alternative medication for rapid tranquilization, need for initial investigations and documentation of the patient's vitals, initiation of antipsychotic therapy without initial monitoring and screening for substance abuse, inappropriate dose at initiation of antipsychotic medications, untreated indication, and incidence of missed doses. Interventions by the clinical pharmacists contributed to improvement in the patient's symptoms prior to hospital discharge. The case proves that it is critical for clinical pharmacists to be involved in the multidisciplinary team during management of patients with psychosis.